Determinant of customer satisfaction in the context of mobile application of online food delivery service - Abd Aziz @ Abdul Majid, Muhammad Faiz (2020)
Using a mobile application, people easy to select any of their favoured restaurant and choose the menu and buy the food easily. In Malaysia, introducing online food delivery application make someone easy to order the food via online platform. In fact, past studies had found that there is demand from customer to ordering food and delivered to their home by using an application because it make easier for customer buy a food that they want from their favourite restaurant. As a result, most of new company have been develop an application as a third party provider that provide an application for restaurant and customers. But there is some issue such as poor quality system configuration, delivery time longer than expected and information was not up to date in the application. Hence, this study was conducted to identify the relationship between independent variables (factors of mobile application) which are ubiquitous connectivity, contextual offer, transaction accuracy and content quality with dependent variable, customer satisfaction, using mobile application of online food delivery service. This study was conducted in two geographical area which is in Melaka and Negeri Sembilan. The research objective is to determine the relationship between independent variables independent variable (ubiquitous connectivity, contextual offer, transaction accuracy and content quality) and dependent variable (customer satisfaction). The data collected has been analysed through software SPSS 23.0 version in order to get reliability analysis, frequency analysis, descriptive analysis and multiple regression analysis. Result showed that there is a significant relationship between transaction accuracy and content quality with customer satisfaction while ubiquitous connectivity and contextual offer did not have significant relationship with customer satisfaction. Content quality is found to be the most influential factors towards customer satisfaction.